2012
DOI: 10.1177/1545968312452470
|View full text |Cite
|
Sign up to set email alerts
|

Observation-to-Imitate Plus Practice Could Add Little to Physical Therapy Benefits Within 31 Days of Stroke

Abstract: These findings suggest that OTI + PP might add little to the benefits of CPT early after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 44 publications
0
79
0
Order By: Relevance
“…An additional 18 studies [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were excluded because they did not have a PEDro score of at least 6. Eleven studies [53][54][55][56][57][58][59][60][61][62][63] were excluded because there was no dosematched control intervention, for comparison with the experimental intervention. Two studies were excluded because the clinical assessments were not masked, or this was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…An additional 18 studies [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] were excluded because they did not have a PEDro score of at least 6. Eleven studies [53][54][55][56][57][58][59][60][61][62][63] were excluded because there was no dosematched control intervention, for comparison with the experimental intervention. Two studies were excluded because the clinical assessments were not masked, or this was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…The two major forms of neurorehabilitation of the paretic arm in chronic stroke based on motor-learning principles are CIMT, and robotics. There are other learning-based approaches, which include action observation [57,58], bilateral priming [59], Arm Ability Training [60], electromyography (EMG)-triggered neuromuscular stimulation [61], and virtual reality [62]. We will not cover these other approaches here in any detail because they have received less experimental attention and because the principles that will be discussed here, in our view, apply to them to a large degree.…”
Section: Motor Learning In Chronic Stroke: It's All About Compensationmentioning
confidence: 99%
“…In rehabilitation, observing actions made by another individual, among other related approaches, can be used to promote activation of damaged motor circuits. While several small-scale clinical studies have found benefits from action observation after stroke 8 , success has been mixed 9 . Our proof-of-concept study was designed to address the lack of basic studies on the neural response to action observation after stroke.…”
mentioning
confidence: 99%